The combined use of steam-treated bentonites and natural zeolites in the oenological refining process. (2nd January 2018) - Mercurio, M.; Bish, D. L.; Cappelletti, P.; de Gennaro, B.; de Gennaro, M.; Grifa, C.; Izzo, F.; Mercurio, V.; Morra, V.; Langella, A.
Abstract: Industrial minerals, particularly bentonites, have long been used in treatments to improve the stability and shelf life of white wines. We evaluated a new combination of rocks and minerals, including steam-treated bentonites and natural zeolites (chabazite and phillipsite), to greatly reduce the risk of protein and tartaric instability of wines. Detailed mineralogical, chemical and electrokinetic studies of these materials were conducted using powder X-ray diffraction (PXRD), X-ray fluorescence (XRF), microporosimetry, BET surface-area analysis and zeta-potential measurements. Several model wine solutions containing Bovine Serum Albumin (BSA) were prepared to evaluate the oenological performance of the rock/mineral combinations. UV-VIS spectrophotometry and ion chromatography were used to evaluate the degree of wine stabilization from the protein and tartaric point of view. The experimental results showed that steam treatment modifies both the microporosity and external surface area of the bentonite. These changes in surface area, along with creation of hydrophobic surfaces, significantly modified the behaviour of the steam-treated bentonites, requiring an increase in the amount of material necessary to bring the protein content to required levels. An important benefit derived from the use of steam-treated bentonites is that the pre-mixing with water before addition to wine is not necessary, as the material is readily dispersed. Finally, the addition of natural zeolites effectively decreased the potassium content, thereby improving the tartaric stability of white wines. In addition, this procedure results in minimal waste, as the bentonite-zeolite mixture can be reused as soil amendments in agriculture.